Enhancing orange-reddish emission of the Sm3+-doped ZnO-B2O3-SLS glasses for the potential glass phosphor materia - Wei Mun Cheong, Wei Mun Cheong; Mohd Zaid, Mohd Hafiz; Yap Wing Fen, Yap Wing Fen; Tan Sin Tee, Tan Sin Tee; Matori, Khamirul Amin i; Zhi Wei Loh, Zhi Wei Loh; Mayzan, Mohd Zul Hilmi (Elsevier, 2023)
In this paper, a series of [Sm2O3]x[(ZnO)0.5 (B2O3)0.1 (SLS)0.4]1-x, where × = 0, 0.01, 0.02, and 0.03 in weight fraction was fabricated via melt-quenching method. The influence of the samarium ion (Sm3+) concentration on the structural and optical properties was investigated. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the samples’ glassy (amorphous) behavior. The optical absorption intensity enhanced as the dopant increased, whereas the optical band gap reduced with the progression of Sm3+ concentration. The sample’s refractive index and Urbach energy range from 2.145 to 2.203 and 0.682 eV to 0.713 eV, respectively. From the photoluminescence studies, 3 wt% Sm3+-doped samples indicate the most intense emission in the orange-reddish region among the other samples. The calculated CIE coordinates for Sm3+ doped ZnO–B2O3–SLS glasses are approximate (0.57, 0.43), near the Amber LED NSPAR 70BS produced by Nichia Corporation. In addition, the CCT of the Sm3+-doped samples at about ~ 1750 K reveals prepared glass samples have bright orange-reddish emission. These findings indicate that Sm3+-doped in ZnO-B2O3-SLS has enhanced its orange-reddish emission and potential as an orange-reddish glass phosphor material in optoelectronic devices such as glass phosphor for LEDs.